Faktor-faktor yang Mempengaruhi Pembelian Impulsif Muslim Gen-Z Saat Tanggal Kembar di Jabodetabek - Rauha, Alda; Nurhasanah, Saniatun (Ekonomis: Journal of Economics and Business, 2025)
This study aims to analyze the influence of promotions, shopping lifestyle, religiosity, and Islamic financial literacy on impulsive purchases on twin dates among Gen-Z Muslims in the Shopee marketplace. This study uses quantitative methods and the types of data used are primary and secondary data distributed through questionnaires. The analysis technique used is a structural equation model (SEM) with the partial least squares (PLS) method. The results of this study indicate that simultaneously there is an influence of promotions, shopping lifestyle, religiosity, and Islamic financial literacy on impulsive purchases on twin dates in the Shopee marketplace. However, partially, the variables of religiosity and Islamic financial literacy do not have a significant effect on impulsive purchases on twin dates in the Shopee marketplace in Jabotabek.